Adequacy, utilization and repayment of society for social service credit on poor women of Mymensingh district in Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2021)
The present study was an attempt to assess adequacy, utilization and repayment of Society for Social Service (SSS) credit on women beneficiaries. Interviewing 90 respondents randomly selected from five villages of Gouripur upazila of Mymensingh district in Bangladesh. The study revealed that both annual income and expenditure of the respondent households have increased after joining the micro credit program of SSS. Average annual income of agriculture and petty business enterprises are Tk. 80726.57 and 74864.14 respectively while average annual expenditure of agriculture and petty business enterprises are Tk. 78776.65 and 67912.37 respectively. Overall annual savings of agriculture and petty business enterprises are Tk. 3733.25 and 8475.09 respectively. Moreover, the women are better at present in respect of social awareness, freedom of attitude, financial freedom and also exercising their right in decision making activities. The study identified some crucial problems such as lack of adequate credit, high rate of interest, burden of old debt, lack of storage and marketing facilities, lack of improved seeds/breed and low price of their products, etc. The findings suggest that the amount of credit should be provided in accordance with their requirement, reduced interest rate and arranging for reasonable price of their products. Finally it was concluded that the SSS credit program benefited the women beneficiaries in respect of increasing income, creating self-employment opportunity, improving social status and at least in reducing the poverty from the study area.Asian Australas. J. Food Saf. Secur. 2021, 5 (1), 1-10